Plotinus on Beauty : Beauty as Illuminated Unity in Multiplicity - Gál, Ota, (Studies in Platonism, Neoplatonism, and the Platonic Tradition ;, 2022)
"In this book, Ota Gál presents a new analysis of Plotinus' conception of beauty, beginning from a close reading of treatises I.6 and V.8, which link beauty with the unified multiplicity of Intellect. This account is subsequently placed in a hierarchical and structural context in VI.2 and VI.6 and connected to illumination in VI.7, enabling us to determine the meaning of the predicate "beauty" at different ontological levels. For Plotinus, beauty is ultimately the illuminated unity in multiplicity of Intellect, which, as the manifestation of the Good, simultaneously enables the soul's ascent and threatens to bind the soul to itself"--